Ultrasonographic Diagnosis of Schistosoma mansoni Eggs in Rectum - Fabio G. Rodrigues; Joao Batista Campos; Nivaldo Hartung Toppa; Steven D. Wexner; Giovanna Dasilva (Case Reports in Infectious Diseases)
Schistosomiasis is a trematode infection endemic in more than 70 countries that affects an estimated 250 million people. We report the case of a 60-year-old healthy female referred for endoscopic ultrasound after rectal examination revealed granular lesions. Ultrasound revealed the presence of deep mucosal nodular lesions with calcified/hyperechoic inclusions. Histologic evaluation has confirmed the final diagnosis of chronic schistosomal colitis. In patients with nonspecific intestinal lesions without a suspected diagnosis of schistosomiasis, endoscopic ultrasound can be enlightening. Schistosomiasis is still an endemic infection in some parts of Brazil and other tropical regions, causing colorectal lesions with unspecific presentation.